á¸iwa-Buddha Doctrine Implementation in Clergy Symbol towards Hindu Society at Lombok - Mustika, I Ketut Cameng (International Research Journal of Management, IT & Social Sciences, 2017)
The present research was intended to reveal á¸iwa-Buddha doctrine implementation in the clergy symbol domain toward Hindu religious society at Lombok. Regarding the research was focused on the background, functions, and meanings of á¸iwa-Buddha doctrine implementation in the clergy symbol to Hindu society at Lombok. An existence background of á¸iwa-Buddha doctrine included the three. First, á¸iwa-Buddha doctrines influence was from Majapahit kingdom period. Second, á¸iwa-Buddha doctrines were diffused by Balinese people during Dalem Waturenggong period at the Gelgel Kingdom. Third, the large deployment was during Karangasem kingdom expanded territory in Lombok. á¸iwa-Buddha doctrine was implemented in the clergy symbol domain had occurred before both doctrines entry Lombok island. á¸iwa-Buddha function doctrines in the religious symbols towards Hindu society at Lombok, related to the fundamentally functions that was used as a basis for the individually and collectively doctrines religion realization. The functions of the á¸iwa-Buddha doctrines implementation in the religious symbols towards Hindu society at Lombok included: philosophies system integration between á¸iwa and Buddhism doctrines, realizing social integrity between adherents of á¸iwa and Buddhists, and improving religious consciousness in divinity aspect of living. An implicit meaning in á¸iwa-Buddha doctrines implementation in the religious symbols towards Hindu society Buddha at Lombok. At relating to the noble values understanding consists in life significance including of religious meaning, cultural meaning, social meaning, and harmony meaning.